Digital Public Pressure And Law Enforcement Independence: An Islamic Criminal Law Perspective - Nurul Etika; Nabilah Yusof (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
In order to assess the quality of justice in managing viral criminal cases in Indonesia, this study creates an integrated analytical framework that takes into account digital public pressure, institutional communication, law enforcement independence, and Jinayah norms. This study examines the chain causal relationship from digital pressure to institutional response and its impact on the independence of law enforcement through the evaluative lens of Islamic criminal law principles using a qualitative literature review socio-legal through content analysis and conceptual analysis. The findings of the analysis indicate that: (1) public digital pressure has a significant impact on the speed and direction of legal responses, but frequently at the expense of objectivity and due process; (2) institutional communication acts as a weak mediator because it is reactive and has not yet been integrated with normative principles; (3) social media trials threaten officials' independence by undermining the presumption of innocence; and (4) the Jinayah principles of procedural justice, dignity protection, maslahah, and ta’zir limitation by legitimate authorities have not yet been operationalised as empirical indicators in the current digital-legal literature. By employing Jinayah as a normative evaluative matrix within the framework of digital public pressure, institutional communication, office holders independence, and the quality of justice, this study closes the research gap. In order to preserve a balance between public accountability and legal integrity in the digital age, it is implied that proactive institutional communication strategies must be rebuilt and Jinayah principles must be included into operational standards for managing viral cases.